2020
DOI: 10.3389/fvets.2020.00628
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus From Goats Are Genetically Heterogeneous and Distinct to Bovine Ones

Abstract: Staphylococcus aureus is one of the major pathogens responsible for intramammary infections in small ruminants, causing severe economic losses in dairy farms. In addition, S. aureus can contaminate milk and dairy products and produce staphylococcal enterotoxins, being responsible for staphylococcal food poisoning. Currently, data on the population structure and the virulence gene patterns of S. aureus strains isolated from goat milk is limited. Therefore, this study aimed at defining Ribosomal Spacer PCR (RS-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(86 reference statements)
0
6
1
Order By: Relevance
“…S. aureus is classified among the most frequent bacterial causative agents of clinical mastitis in small ruminants [54][55][56][57]. The isolation frequencies in the present study were low: two strains out of 120 samples in group A and six strains out of 120 samples in group B.…”
Section: Discussioncontrasting
confidence: 60%
“…S. aureus is classified among the most frequent bacterial causative agents of clinical mastitis in small ruminants [54][55][56][57]. The isolation frequencies in the present study were low: two strains out of 120 samples in group A and six strains out of 120 samples in group B.…”
Section: Discussioncontrasting
confidence: 60%
“…The majority, 17 of 20 (85%) of our isolates belonged to three CCs: CC151, CC133, and CC97, which have been reported as common bovine-associated complexes ( Hoekstra et al, 2020 ; Naushad et al, 2020 ). Two of our isolates in the peracute group belonged to CC522, which is commonly found in isolates from mastitis in small ruminants ( Kahila Bar-Gal et al, 2015 ; Romano et al, 2020 ). A recent review ( Matuszewska et al, 2020 ) showed that CC522 has thus far been found only in small ruminants.…”
Section: Discussionmentioning
confidence: 84%
“…CC522 was not detected by Hoekstra et al (2020) , nor by Naushad et al (2020) . Both CC522 and CC133 are commonly found in small ruminants ( Kahila Bar-Gal et al, 2015 ; Romano et al, 2020 ). Neither of the herds from which the CC522 isolates in our study originate has any association with small ruminants, nor are these farms located adjacent to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive typing of S. aureus isolates, the other most prevalent lineages reported in wild ruminants in several European countries, namely CC97, CC130 and CC133 (Monecke et al., 2016 ), were not detected in our study area. This result was unexpected because CC97 and CC130 have been reported in Western Italian Alps in roe deer and chamois (Luzzago et al., 2014 ) and might also represent livestock‐associated lineages in Italy (Feltrin et al., 2016 ; Romanò et al., 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…were not detected in our study area. This result was unexpected because CC97 and CC130 have been reported in Western Italian Alps in roe deer and chamois (Luzzago et al, 2014) and might also represent livestock-associated lineages in Italy (Feltrin et al, 2016;Romanò et al, 2020).…”
Section: Ta B L Ementioning
confidence: 89%